Pengaruh faktor demografi terhadap tingkat kepatuhan wajib pajak orang pribadi pada Kantor Pelayanan Pajak Pratama Sekayu - Ardiyanto, Redhy; Saputri, Harni Septianda; Saputri, Yosi Eka; Haryadi, Haryadi; Rahayu, Sri (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
Taxation is a form of state obligation in the context of community participation in financing growth. The views and behavior of WP are affected by several factors, including demographics. Demographic factors such as gender, work, and socio-economic status can explain the possibility of a person's actions and motivations. This study aims to determine the effect of demographic factors on the level of compliance of individual taxpayers in Sekayu District at the Sekayu Primary Tax Service Office. The research method used in this study is the quantitative method and uses a model based on multiple regression analysis. SPSS is used to analyze the data. The results of the study stated that the interaction between sex, work, and financial status influenced the compliance of one's taxpayers. Factors such as sex, work, and socio-economic status contribute to the disparity in taxpayer compliance between individuals.